Initial Ability in Online Learning Process of Elementary School Teachers; Case Studies in Riau Province - Radeswandri Radeswandri; Rian Vebrianto; Mery Berlian; Musa Thahir; Cahyani Elvira (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThis study describes the initial ability of teachers in carrying out online learning activities. This research was conducted through survey research involving 154 elementary school teachers in Pelalawan and Rengat Regencies, Riau Provinces as the research samples were taken by purposive sampling. Research data were obtained through a survey using google forms and distributed via WhatsApp. Data analysis was carried out descriptively and inferentially using SPSS version 26. Based on the data analysis, it was identified that 97 teachers (63%) choose a combination learning model between offline and online as the most frequently learning model used during the covid-19 pandemic. In carrying out the learning process, 93 teachers (60.4%) chose schools as teaching locations. Regarding the quality of the internet in schools, 110 teachers (71.4%) assessed that the quality of the internet in schools was good and could support learning activities. Furthermore, teachers also apply various ways of teaching online learning, for example, 50 teachers (32.5%) choose to provide interactive material through online media and 45 teachers (29.2%) ask students to learn to use textbooks and give assignments to students in the form of assignments on worksheets, projects, books, etc. The main obstacle for teachers during online learning is that they find it difficult to observe student progress and have difficulty communicating with parents. The efforts made by teachers to adapt online learning is by providing materials/tasks and establishing basic competencies according to student needs.Keywords: teacher ability, online learning, covid-19 pandemic.Â AbstrakPenelitian ini mendeskripsikan kemampuan awal guru dalam melaksanakan kegiatan pembelajaran online. Penelitian ini dilakukan melalui penelitian survei yang melibatkan 154 guru SD di Kabupaten Pelalawan dan Rengat, Provinsi Riau sebagai sampel penelitian yang diambil secara purposive sampling. Data penelitian diperoleh melalui survei menggunakan google form dan disebarluaskan melalui WhatsApp. Analisis data dilakukan secara deskriptif dan inferensial menggunakan SPSS versi 26. Berdasarkan analisis data diketahui bahwa 97 guru (63%) memilih model pembelajaran kombinasi antara offline dan online sebagai model pembelajaran yang paling sering digunakan selama masa pandemi covid-19. Dalam melaksanakan proses pembelajaran, 93 guru (60,4%) memilih sekolah sebagai lokasi mengajar. Terkait dengan kualitas internet yang ada di sekolah, 110 guru (71,4%) menilai bahwa kualitas internet yang ada di sekolah sudah baik dan dapat mendukung kegiatan pembelajaran. Selanjutnya, guru juga menerapkan berbagai cara dalam mengajar pembelajaran online, misalnya 50 guru (32,5%) memilih memberikan materi interaktif melalui media online dan 45 guru (29,2%) meminta siswa belajar menggunakan buku teks dan memberikan tugas kepada siswa berupa tugas pada LKS, proyek, buku, dan lain-lain. Kendala utama guru selama pembelajaran online adalah mereka menemukan kesulitan dalam mengamati perkembangan siswa dan kesulitan dalam berkomunikasi dengan orang tua. Adapun upaya yang dilakukan guru untuk menyesuaikan pembelajaran online adalah dengan menyediakan materi/tugas dan menetapkan kompetensi dasar sesuai kebutuhan siswa.Kata kunci: kemampuan guru, pembelajaran online, pandemic covid-19.